Technical Assistance for the Process of Making Liang Tea as a Healthy Drink in The PKK (Family Welfare Development) Organization of West Kalimantan Province Administrator - Dewi, Yohana Sutiknyawati Kusuma; Fadly, Dzul; Syamsi, Wisi Wilanda; Rahmalia, Winda; Sutignya, Thomas Candra Wasis Agung (Journal of Saintech Transfer, 2023)
Community service regarding the Technology of Liang Tea Making as a Health Drink was carried out by a Team of Lecturers from the Food Science and Technology Study Program, Faculty of Agriculture, Tanjungpura University (UNTAN) at the PKK Office. The partner of this activity is the West Kalimantan Province PKK. The problems faced by the skills and knowledge of Provincial PKK members as facilitators for members of the PKK organization at the Regency, Sub-District level which they assist in making health drinks as well as traditional Pontianak drinks that are competitive are still limited. The implementation method used is socialization in the form of counseling, training, mentoring, evaluation and monitoring. The results of the activity achieved were 80% of participants during the socialization increased their knowledge based on the results of question and answer through questionnaires, 10 training participants were able to make tea burrows correctly, 5 trainees would use tea burrows for their family’s functional drinks. The continuation of this activity is expected to produce new facilitators for members of the PKK organization and initiate PKK members for product commercialization.